PENYULUHAN KEWIRAUSAHAAN PRODUKSI MAKANAN EKSTRUDAT JAGUNG DI DK. PLOSOKEREP DS. PRAWOTO KEC. SUKOLILO KAB. PATI - Muhammad Subridan; Muh Amin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The purpose of community service is to provide knowledge about entrepreneurship for the farmers in Hamlet Plosokerep Prawoto Village Sukolilo District Pati District 90% of its citizens rely on his fate on agriculture. The type of agriculture that is the mainstay of the partner community is corn farming. In addition to corn, it can be said almost non-existent due to the condition of the area in mountainous areas that are difficult to find groundwater. The best crops in the area are maize. The condition of the remote Plosokerep dukuh area with the village village and separated from the neighboring village may provide the backwardness of local knowledge. Citizens who are 90% not graduated from elementary school it has always been 80% relying on corn farming without a side business. Through this community service has been done counseling about entrepreneurship in the hope to open the local community to entrepreneurship and can increase revenue. In this service has been taught how the process of making extruded snack foods from local raw materials (corn) to the way of marketing. The outreach results are well-received by the community and partners feel the need for knowledge of entrepreneurship. Keywords: Counseling, Entrepreneurship, Farmers, Production of Extruded Light Foods. Corn Extrudate